Dynamic behavior of an agricultural power take-off driveline for rattle noise reduction: Part 1. Effect of spline tolerance on the power take-off rattle noise. (December 2021) - Choi, Chanho; Ahn, Hyoungjong; Park, Young-Jun; Kim, Su-chul; Yu, Jihun
Highlights: Dynamic behavior analysis to predict PTO driveline gear rattle noise levels. The dynamic behavior changes according to rotation speed. These changes resulted in a rapidly-occuring jumping phenomenon at specific speeds. Dynamic behavior changes depend on engine excitation-component amplification. The gear rattle noise levels were reduced by approximately 10.9 dB(A). Abstract: An agricultural tractor has a power take-off (PTO) driveline that is directly connected to the engine to improve its power transmission efficiency. The PTO driveline comprises various mechanical components coupled by a spline joint. The spline coupling tolerance causes collisions between various mechanical parts of the PTO driveline and affects gear collision, thereby causing rattle noise. Therefore, the aim of this study is to conduct a dynamic behavior analysis to predict the gear rattle noise level of a PTO driveline. The dynamic behavior of the PTO driveline was analyzed through 1D simulations, and the results confirmed that the dynamic behavior changes according to rotation speed. Experimental verification of the dynamic behavior analysis results confirmed that the dynamic behavior changes as the main engine excitation-component amplification changes and then decreases at a relatively high rotation speed. Additionally, the dynamic behavior changes of the PTO driveline resulted in a jumping phenomenon that occurs rapidly at a specific rotation speed. The amplification of the engine's main components was reduced from 3 to 4 times to 1.2 times owing to the jumping phenomenon; the noise level of the gear rattle was also reduced by approximately 10.9 dB(A).